Schinus terebinthifolius (Brazilian Peppertree) extract used as antifungal to control Candida spp. in planktonic cultures and biofilms - Viegas, Daiane de Jesus; Amêndola, Isabela; Botrel, Tássia Marchetti; de Oliveira, Felipe Eduardo; Figueira, Leandro Wagner; Sper, Fábia Lugli; de Oliveira, Jonatas Rafael; de Oliveira, Luciane Dias (Brazilian Dental Science, 2020)
Objective: The use of medicinal plants may be an alternative method for the control of Candida spp. responsible for human infections. This study evaluated the antifungal effect of Schinus terebinthifolius extract (Brazilian Peppertree) on C. albicans, C. dubliniensis, C. glabrata, and C. krusei planktonic cultures and biofilms. Material and Methods: Minimum inhibitory concentration (MIC) and minimum fungal concentration (MFC) of the plant extract were determined by the broth microdilution method. Biofilms formed in microplate wells were exposed to the extract for 5 min (50, 100 and 200 mg/mL) or 24 h (25, 50 and 100 mg/mL). After determination of colony-forming units per milliliter (CFU/mL), the data were analyzed by one-way ANOVA and Tukey’s Test (P ? 0.05). Results: Different MIC (mg/mL) were found, such as 0.39 (C. dubliniensis), 1.56 (C. albicans), and 3.13 (C. glabrata and C. krusei). Besides, MFC (mg/mL) of 0.78 (C. dubliniensis) and 3.13 (C. albicans, C. glabrata and C. krusei) were also observed. Regarding the biofilms, significant reductions (log10) were found after 5 min and 24 h exposure to the plant extract, compared to the control group. However, C. dubliniensis was significantly affected only in 24 h treatment. Conclusion: S. terebinthifolius extract presented a significant antifungal effect on C. albicans, C. dubliniensis, C. glabrata, and C. Krusei both in planktonic cultures and biofilms.